Effectiveness of primary care psychological therapy services for the treatment of depression and anxiety in people living with dementia: Evidence from national healthcare records in England. (October 2022) - Bell, Georgia; Baou, Celine El; Saunders, Rob; Buckman, Joshua E. J; Charlesworth, Georgina; Richards, Marcus; Brown, Barbara; Nurock, Shirley; Michael, Stuart; Ware, Paul; Aguirre, Elisa; Rio, Miguel; et al.
Summary: Background: Depression and anxiety are common and deleterious in people living with dementia (PLWD). It is currently unknown whether routinely provided psychological therapy can help reduce these symptoms in PLWD. This study aimed to investigate improvements in depression and anxiety symptoms over the course of therapy offered in primary care psychological therapy services in PLWD and to compare outcomes to people without dementia. Methods: National data from Improving Access to Psychological Therapies services (IAPT) across England linked with Hospital Episode Statistics data, the Mental Health Services Dataset, and HES-ONS mortality data were used to identify 1, 549 PLWD who completed a course of psychological treatment in IAPT between 2012-2019 and a propensity score matched control group without identified dementia. Outcome measures included pre-post intervention changes in depression (PHQ-9) and anxiety (GAD-7) symptoms and therapy outcomes (reliable improvement, recovery, deterioration). Findings: Symptoms of depression ( t (1548)=31·05, p <·001) and anxiety ( t (1548)=30·31, p <·001) improved in PLWD over the course of psychological therapy with large effect sizes (depression: d =-0·83; anxiety: d =-0·80). However, PLWD were less likely to reliably improve (OR=·75, 95%CI[·63, ·88], p<·001) or recover (OR=·75, 95%CI[·64, ·88], p =·001), and more likely to deteriorate (OR=1·35, 95%CI[1·03, 1·78], p= ·029) than a matched control sample without dementia. Interpretation: Psychological therapy may be beneficial for PLWD with depression or anxiety, but it is currently not as effective as for people without dementia. More research is needed to improve access to psychological therapies and to understand this discrepancy and how therapies can be adapted to further improve outcomes. Funding: This work was supported by the Alzheimer's Society.